Predicting of Tsunami Inundation Area based on Propagation and Runup Numerical Model in Pacitan City - Agus Suharyanto; Alwafi Pujiraharjo; Adipandang Yudono; Keisuke Murakami; Chikashi Deguchi (Syiah Kuala University, 2012)
Pacitan city represents one of the regions residing in South East Java ProvinceIndonesia about which on direct with Indian Ocean. In this area there is a meeting of plate of Indo-Australia with plate of Eurasia which is if colliding head-on potency can generate tsunami. Seeing this existing condition, it is needed a study to know how susceptible level of South East Java Province regional to get disaster of tsunami. Based on the tsunami was occurred in Aceh Indonesia on December 26, 2004 was killed more than 200.000 peoples, the tsunami disaster management become very important to study. One of the studies ishow to predict the tsunami runup along shoreline of southern beach of East Java Province Indonesia. According to the geological data, area of east Java Ocean has high potential of earthquake. The history shows that there are many time tsunami occurred in East Java. Based on the initial study, one of the areas predicted as dangerous area for the tsunami is Pacitan city. To minimize the effect of tsunami hazard, prediction of inundation area base on the numerical model simulation of tsunami runup was done for Pacitan city. In this research predicting of inundation area caused by tsunami was studied. GIS was used astool to predict the inundation area. From this research it can be shown that numerical model of tsunami can be used to predict the runup. Base on runup elevation, inundation area can be predicted well by using GIS